Development of an instrument to assess social functioning in dementia: The Social Functioning in Dementia scale (SF‐DEM). Issue 1 (23rd February 2017) - Sommerlad, Andrew; Singleton, David; Jones, Rebecca; Banerjee, Sube; Livingston, Gill
Abstract: Introduction: Social functioning is a core domain in the life of people with dementia, but there is no accepted instrument to measure it. We aimed to develop the Social Functioning in Dementia (SF‐DEM) scale and test its psychometric properties for assessing social function in people with dementia. Methods: We interviewed people with mild dementia and family caregivers to develop patient and caregiver‐rated SF‐DEM versions and refined them through interviews with health care professionals. We tested its psychometric properties in 30 dyads of people with dementia and family caregivers. Results: Both SF‐DEM versions had content validity and demonstrated concurrent validity against a single item rating overall social functioning (patient rated r  = 0.42, 95% CI [0.07–0.68]; caregiver rated r  = 0.59, 95% CI [0.29–0.78]). All participants found it acceptable. Analyses showed reliability (test–retest, inter‐rater, internal consistency) and indications of responsiveness to change. Discussion: SF‐DEM shows promise as a valid, reliable, acceptable measure of social functioning in dementia. Highlights: Social function is key to dementia diagnosis and important to patients and families. SF‐DEM is the first assessment tool for measuring social functioning in dementia. In SF‐DEM, core social functioning domains are assessed by self‐ or proxy‐report. These measures are acceptable to clinicians and respondents, and are reliable. SF‐DEM has content and concurrent validity in mild dementia.